Intake Vaccinations Reduced Signs of Canine Respiratory Disease During an Outbreak at an Animal Shelter - Andrukonis, Allison; Brown, Kelsea M.; Hall, Nathaniel J.; Protopopova, Alexandra (Frontiers in Veterinary Science, 2021)
Animal shelters provide an ideal environment for the spread of disease. Dogs are often housed in close quarters with others of unknown vaccine histories, and experience high levels of sustained stress. As a result, Canine Infection Respiratory Disease (CIRD) is often prevalent and difficult to control. The aims of this study were to 1) identify specific pathogens responsible for CIRD in a city shelter in West Texas, USA, and 2) determine whether intake vaccinations decrease proportion of dogs exhibiting signs of CIRD even during an outbreak. A laboratory analysis of conjunctival, pharyngeal, and nasal swabs (n = 15 dogs) and fecal samples (n = 6 kennels) showed prevalence of various CIRD pathogens. All fifteen dogs tested positive for at least one pathogen, with the most prevalent pathogen being Canine Distemper Virus (CDV; n=12). All of the kennels (n=6) tested positive for Canine Distemper Virus. Health data on dogs (n = 1258) over the age of six weeks were assessed from May to August 2017. Beginning in July, both stray and owner-surrendered dogs were vaccinated upon intake, which differed from the previous policy. For each day in the study, we calculated the proportion of dogs in each nasal discharge category, the proportion of dogs observed coughing, and the mean fecal score across all dogs. We conducted a linear regression between the proportion of the shelter vaccinated and the proportion of dogs coughing. At the beginning of the vaccination phase, approximately 25% of the dogs were coughing. However, as the proportion of the dogs vaccinated increased, the proportion of dogs coughing decreased. There was a significant decrease of 7% of the proportion of dogs coughing when vaccination was at least at 90% compared to when it was less than 90%. These data suggest that the shelter in this study was experiencing a CIRD outbreak, with CDV being primary pathogen, and that it is possible to substantially reduce illness by implementing a vaccination on intake protocol. The current study provides strong support for the importance of vaccination in animal shelter welfare.